Lateral size dependence of piezoresistivity and photoconductivity in TMD networks (2024)
Transition metal dichalcogenides (TMDs) are a family of layered bidimensional (2D) materials which find great interest in fields such as medicine, energy conversion, water treatment, and electronics. Moreover, the most impressive feature of this family is the transition to a direct semiconductor as the material is fully exfoliated. Nevertheless, the interesting properties that arise as the number of layers reduce, do not necessarily persist when the nanosheets are printed on substrates to form networks. Therefore, further research on the networks and the influence of the nanosheets’ dimensions is valuable for scaling up prospects. Regarding the production process of TMD nanosheets, good quality dispersions can be obtained by liquid phase exfoliation (LPE). Moreover, the long processing times that this process requires can be reduced by mediating the exfoliation through intercalation of lithium ions. Both techniques were successfully applied to tungsten disulfide (WS2) and molybdenum disulfide (MoS2) powders to obtain concentrated dispersions. However, these dispersions are characterized by a wide distribution of sizes and thicknesses. Selecting the lateral size and thickness was successfully done by liquid cascade centrifugation (LCC). The morphological analysis by scanning electron microscopy (SEM) allowed to characterize the average and standard deviation of the distribution of the unselected and selected dispersions. Furthermore, UV-Vis, FTIR, and Raman spectroscopy allowed to distinguish the optical properties and the vibrational features of both TMDs. Characteristic Raman signals are layer dependent, thus specific features of this spectrum can be utilized as a metric. X-ray diffraction was conducted on all devices, which gave a tool to distinguish WS2 networks, conformed by two or three TMD layers which are mostly 2H-hexagonally-structured, to MoS2 networks, conformed by more than five layers which showcases a mixture of a rhombohedral (3R) and a hexagonal (2H) structure. Piezoresistivity, which is the change of resistance induced by an applied strain, matters as an important effect when designing sensors applied in medicine, energy conversion, opto-electronics and so on. It is known that strain alters the band structure of TMDs and also tune transitions between different crystal structures. Moreover, applying strain to semiconductors would change their electronic properties which could be modeled through their piezoresistivity tensor. The figure of merit that measures how much the resistivity changes when strain is applied is the gauge factor (GF). In networks, this is modeled as a sum of the nanosheet intrinsic GF and the change of the junction resistance between nanosheets due to strain. In this thesis the GF of the devices was obtained through their transport characteristics when applying uniaxial strain, both at a tensile and a compressive setup, by using a three-beam bending machine. Hereby the first report of a transition from a positive GF to a negative one, when applying uniaxial strain to WS2 networks as the lateral size increases, and a transition from negative GF to a positive one, when compression is applied to MoS2 networks as lateral size increases is shown. Photoconductivity is an important feature of semiconductors that finds major attention in the fields of solar cells, hydrogen and oxygen evolution reactions, and photodetectors. This feature involves a change of density of charge carriers induced by light, which is dependent on the generation of light-induced carriers and the recombination of excitons. In this thesis, the photoconductivity of printed devices was measured by using a xenon lamp inside an obscure chamber. Molybdenum disulfide-based devices show higher responsivity as compared with tungsten disulfide devices, which is attributed to an increased light absorption and hydroxyl groups attached to the surface of the MoS2 networks that enhance the photoconductivity by increasing the carrier lifetimes. Furthermore, the responsivity of the devices behaves similarly to the conductivity, which is modeled as networks of pairs of nanosheets and junctions through percolative paths. Finally, this is the first report that shows that the response time of the devices increase with lateral size.